A method for preparing hemp biomass thermal insulation material

By adding trichloro (2-chloroethyl)silane to the hemp rod core powder to form a silicon oxygen internal support structure, the problems of low strength and poor fire resistance of the hemp rod core powder are solved, and the effect of improving strength and fire resistance is achieved.

CN119735826APending Publication Date: 2025-04-01ZHEJIANG IND POLYTECHNIC COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411912579.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing hemp rod core powder has low strength and poor fire resistance.

Method used

By adding trichloro(2-chloroethyl)silane to the hemp rod core powder as the permeable and adsorbable material, an internal silicon oxygen support structure is formed, and the external porous silicon oxygen structure is combined to form an integrated hemp biomass insulation material.

Benefits of technology

It improves the stability and antibacterial properties of the hemp rod core powder, enhances its support strength and fire resistance, and achieves lightweight, flame retardant and heat insulation effects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of building materials, and specifically relates to a method for preparing a hemp biomass thermal insulation material, which uses trichloro (2-chloroethyl) silane to form a silicon oxide film support on the inner surface of hemp stalk core powder, and forms a porous silicon oxide shell on the surface of the hemp stalk core powder, and finally uses trichloromethyl silane to hydrolyze and polycondense on the surface to form a silicon oxide blocking film to obtain a hemp biomass thermal insulation material. The present invention solves the problems of low strength and poor fire resistance of the existing hemp stalk core powder, uses trichloro (2-chloroethyl) silane as a permeable and adsorbable material, and forms a silicon oxide internal support in the hemp stalk core powder, which not only ensures the pore permeability of the hemp stalk core powder itself, and ensures the stability of its own antibacterial properties, but also the support of the silicon oxide film can improve the stability of the hemp stalk core powder, and cooperates with the external porous silicon oxide structure to form an integrated structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to a method for preparing a hemp biomass thermal insulation material. Background Art

[0002] Thermal insulation materials are a type of material that is resistant to heat flow. They are usually lightweight, loose, porous, and fibrous materials. They are widely used in many fields, including construction, industry, aerospace, and other fields. In the construction field, the use of thermal insulation materials can reduce the phenomenon of alternating hot and cold in the room, maintain a constant indoor temperature, and thus reduce energy consumption. The thermal insulation materials are mainly rock and slag insulation materials, petrochemical and coal chemical products. However, the processing environment temperature of rock and slag insulation materials is relatively high, resulting in serious consumption. At the same time, high temperatures will bring about the emission of various pollutants, resulting in their generally unsatisfactory environmental performance; petrochemical and coal chemical products are often non-renewable, and most of the products are flammable. Flame retardants need to be added to make the products meet the combustion performance of B1 or above specified in the standard, resulting in increased costs. However, when a fire occurs, these products will still release toxic gases, forming serious secondary pollution. With the continuous deepening of research on biomass materials, hemp insulation materials have emerged. Hemp insulation materials have been widely used due to their hollow structure, low cost, low density, low thermal conductivity, etc., and are increasingly valued due to their own advantages such as renewability and simple preparation process. However, hemp insulation materials have problems such as low strength and poor fire resistance. Summary of the invention

[0003] In view of the problems in the prior art, the present invention provides a method for preparing a hemp biomass thermal insulation material, which solves the problems of low strength and poor fire resistance of the existing hemp stalk core powder. Trichloro(2-chloroethyl)silane is used as a permeable and adsorbable material to form a silica internal support in the hemp stalk core powder, which not only ensures the pore permeability of the hemp stalk core powder itself and the stability of its own antibacterial properties, but also the support of the silica film can improve the stability of the hemp stalk core powder, and cooperate with the external porous silica structure to form an integrated structure.

[0004] In order to achieve the above technical objectives, the technical solution of the present invention is:

[0005] A method for preparing a hemp biomass thermal insulation material comprises the following steps:

[0006] Step 1, grinding the hemp stalk core, and obtaining hemp stalk core powder with uniform particle size after sieving, wherein the grinding pressure is 0.5-0.8MPa, the temperature is 20-30°C, and the particle size of the hemp stalk core powder is 1-2mm. In this step, the hemp stalk core is crushed by grinding to form particles with relatively similar particle sizes, and the particles with large particle size deviation are removed by sieving, so as to obtain more refined hemp stalk core powder; this treatment method not only refines the particles of the hemp stalk core to form fine particles, but also homogenizes the fine particles by sieving;

[0007] Step 2, adding trichloro(2-chloroethyl)silane to ether and stirring evenly, then adding hemp stalk core powder and ultrasonically treating it for 20-30 minutes, filtering and drying to obtain coated hemp stalk core powder, the concentration of trichloro(2-chloroethyl)silane in ether is 100-140g / L, the stirring speed is 200-400r / min, the mass ratio of the hemp stalk core powder to the ether is 1:15-20, the temperature of the ultrasonic treatment is 5-10°C, the ultrasonic frequency is 70-90kHz, the drying adopts reduced pressure drying, and the pressure is large The air pressure is 90% and the temperature is 20-25° C. In this step, the good solubility of trichloro(2-chloroethyl)silane in ether is used to form a homogeneous low-concentration dispersion, and the hemp stalk core powder is added at this time. The hemp stalk core powder has good adsorption and can adsorb trichloro(2-chloroethyl)silane to achieve internal coating of the hemp stalk core powder. In the decompression drying after filtration, the volatility of ether itself is improved under the action of pressure and temperature, ensuring that ether is removed from the hemp stalk core powder, thereby forming the hemp stalk core powder coated with trichloro(2-chloroethyl)silane.

[0008] Step 3, allowing the coated hemp stalk core powder to stand for 30-60 minutes, then heating and allowing it to stand for 1-2 hours to obtain modified hemp stalk core powder, wherein the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8-10:1, the standing temperature is 20-30°C, the atmosphere of the heating and standing is a nitrogen atmosphere, and the speed of nitrogen purging is 10-20mL / min, and the temperature is 80-90°C; this step utilizes the hygroscopicity of the hemp stalk core powder to adsorb water vapor in the atmosphere, and during the water vapor adsorption process, the trichloro(2-chloroethyl)silane in the hemp stalk core powder is in-situ hydrolyzed to form trihydroxy(2-hydroxyethyl)silane, and after the in-situ hydrolysis is completed, the water vapor in the air is removed by nitrogen purging, and in the subsequent heating and standing, the trihydroxy(2-hydroxyethyl)silane forms an in-situ polycondensation reaction, thereby obtaining a modified hemp stalk core powder of trihydroxy(2-hydroxyethyl)silane polycondensate;

[0009] Step 4, adding polyvinyl pyrrolidone to ethanol, then adding modified hemp stalk core powder, low-temperature ultrasound for 20-30 minutes, reducing pressure and concentrating to viscosity, filtering and drying and surface spraying to obtain filled hemp stalk core powder, the concentration of polyvinyl pyrrolidone in ethanol is 400-600g / L, the mass ratio of the modified hemp stalk core powder to polyvinyl pyrrolidine is 1:3-4, the ultrasonic frequency of low-temperature ultrasound is 80-100kHz, the temperature is 5-10°C, the temperature of the reduced pressure concentration is 70-75°C, the pressure is 80-90% of the atmospheric pressure, and the drying temperature is 80-90°C; the surface spraying uses distilled water, and the spraying speed is 10-20mL / min, In this step, the solubility of polyvinyl pyrrolidone in ethanol is used to form a dissolving solution, and after the modified hemp stalk core powder is added, ultrasonic treatment is performed to ensure that the internal pores of the hemp stalk core powder and the solution are transparent, and the bubbles in the internal pores are completely removed; the reduced pressure concentration can slowly penetrate the ethanol and gradually increase the concentration. In this process, the polyvinyl pyrrolidone gradually invades the pore structure of the modified hemp stalk core powder. With the increase of viscosity, the pores in the modified hemp stalk core powder can be basically completely filled, and the polyvinyl pyrrolidone in the modified hemp stalk core powder is fixed by filtering and drying. In the surface spraying of water, the polyvinyl pyrrolidone on the surface will be gradually removed to obtain a composite modified hemp stalk core powder with internally blocked polyvinyl pyrrolidone;

[0010] Step 5, adding ethyl cellulose and trichloromethylsilane to ether and stirring evenly to form a solution, and adding ammonium carbonate and filling hemp stalk core powder, rapidly stirring and then granulating and drying to obtain composite particles; the mass ratio of ethyl cellulose to trichloromethylsilane is 1:2-4, and the mass ratio of ethyl cellulose to ether is 1:6-8, the stirring speed is 300-500r / min, the ammonium carbonate is micron ammonium carbonate, the addition amount is 40-50% of ethyl cellulose, the mass ratio of filling hemp stalk core powder to trichloromethylsilane is 1:0.8-1.0, and the stirring speed of the rapid stirring is 2000-3000r / min. min, the granulation and drying temperature is 50-60°C, and the particle size of the composite particles is 5-6mm; this step utilizes the solubility of ethyl cellulose and trichloromethylsilane in ether to form a homogeneous dispersion, and at the same time, ammonium carbonate and the filling hemp stalk core powder are insoluble in ether, and ethyl cellulose has good dispersibility in ether, which can ensure that ammonium carbonate, the filling hemp stalk core powder and trichloromethylsilane form a homogeneous dispersion. In the subsequent granulation and drying, ethyl cellulose, ammonium carbonate, the filling hemp stalk core powder and trichloromethylsilane are mixed to form composite particles, and the ether is evaporated and removed under temperature conditions during drying, thereby forming composite particles;

[0011] Step 6: let the composite particles stand for 1-3 hours, then spray trichloromethylsilane ether solution on the surface of the composite particles, dry and let stand for 1-2 hours to obtain prefabricated composite particles, the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 10-12:1, the temperature is 5-10°C, the concentration of trichloromethylsilane in ether is 100-200g / L, and the spray volume is 2-5mL / cm 2 The drying temperature after drying and standing is 35-40°C, the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 9-10:1; this step uses a standing method to hydrolyze the trichloromethylsilane in the composite particles in situ, and ethyl cellulose is insoluble in water and will not form water vapor deposition. Therefore, when the trichloromethylsilane ether solution is sprayed, the trichloromethylsilane will not be directly hydrolyzed, but the solubility of ether and ethyl cellulose is used to ensure the penetration of trichloromethylsilane, and the deposited and infiltrated trichloromethylsilane is hydrolyzed in situ by standing after drying, and the ether is rapidly volatilized by temperature reduction; at the same time, the infiltrated trichloromethylsilane hydrolyzate and the original trichloromethylsilane hydrolyzate belong to the same substance and have good permeability.

[0012] Step 7, subjecting the prefabricated particles to a constant temperature treatment for 1-3 hours, and then placing them in ethanol for ultrasonic treatment for 20-30 minutes, and then taking them out and subjecting them to a constant temperature sintering treatment for 20-30 minutes to obtain a hemp biomass insulating material, wherein the temperature of the constant temperature treatment is 70-90°C, the mass ratio of the ethanol to the prefabricated particles is 10:1-2, the temperature of the ultrasonic treatment is 20-40°C, the frequency is 70-90kHz, and the temperature of the constant temperature sintering is 400-450°C; in this step, the trihydroxymethylsilane hydrolyzed in situ after infiltration is subjected to in-situ condensation by a constant temperature treatment method, and is connected with the silicon oxide material of the framework system to form a silanol condensation structure, thereby forming surface pores of the entire thermal insulation material; in the ultrasonic treatment of ethanol, ethanol dissolves ethyl cellulose and polyvinyl pyrrolidone, and flows out through the refined pores on the surface, thereby forming a porous structure of the thermal insulation material, and with the temperature of the constant temperature sintering, the residual ethyl cellulose and polyvinyl pyrrolidone are completely removed.

[0013] The hemp biomass thermal insulation material prepared by the above method has hemp stalk core powder as the core, porous silicon oxide film as the inner support frame, porous silicon oxide structure as the outer expansion structure, and silicon oxide material as the plugging surface film. The hemp biomass thermal insulation material has a good pore structure inside, which is better than the supporting strength of the hemp stalk core powder. At the same time, the silicon oxide plugging surface film shows excellent silanol activity, which can form good connection activity in building materials. When mixed with concrete, it can form a stable curing reaction to achieve lightweight building materials. At the same time, the hemp stalk core powder contains antibacterial substances, which has an excellent antibacterial effect. The adsorption of the hemp stalk core powder itself and the repellency of the silicon oxide material to most bacteria ensure that the internal bacteria are deposited in the core powder and killed by the hemp stalk core powder, effectively preventing the corrosion of bacteria and microorganisms.

[0014] It can be seen from the above description that the present invention has the following advantages:

[0015] 1. The present invention solves the problems of low strength and poor fire resistance of the existing hemp stalk core powder. Trichloro(2-chloroethyl)silane is used as a permeable and adsorbable material to form a silica internal support in the hemp stalk core powder, which not only ensures the pore permeability of the hemp stalk core powder itself and the stability of its own antibacterial properties, but also the support of the silica film can improve the stability of the hemp stalk core powder, and cooperate with the external porous silica structure to form an integrated structure.

[0016] 2. The present invention uses methyltrichlorosilane as a silicon-oxygen precursor, which can not only form a silicon-oxygen connection structure and provide excellent support and flame retardancy, but also the surface of the silicon-oxygen material is rich in silanol groups, showing excellent reactivity and meeting subsequent use requirements.

[0017] 3. The present invention uses silicon oxide material as a plugging surface membrane to form an internal plugging of the entire hemp biomass thermal insulation material, and cooperates with the subsequent use of concrete to completely seal the entire hemp biomass thermal insulation material, thereby achieving lightweight, flame retardant and heat insulating effects. DETAILED DESCRIPTION

[0018] The present invention is described in detail with reference to the embodiments, but no limitation is imposed on the claims of the present invention.

[0019] Example 1

[0020] A method for preparing a hemp biomass thermal insulation material comprises the following steps:

[0021] Step 1, grinding the hemp stalk core to obtain hemp stalk core powder with uniform particle size after sieving, the grinding pressure is 0.5 MPa, the temperature is 20° C., and the particle size of the hemp stalk core powder is 1 mm;

[0022] Step 2, adding trichloro(2-chloroethyl)silane to ether and stirring evenly, then adding hemp stalk core powder and ultrasonically treating it for 20 minutes, filtering and drying to obtain coated hemp stalk core powder, wherein the concentration of trichloro(2-chloroethyl)silane in ether is 100 g / L, the stirring speed is 200 r / min, the mass ratio of the hemp stalk core powder to the ether is 1:15, the temperature of the ultrasonic treatment is 5° C., the ultrasonic frequency is 70 kHz, and the drying adopts reduced pressure drying, and the pressure is 90% of the atmospheric pressure, and the temperature is 20° C.;

[0023] Step 3, leaving the coated hemp stalk core powder to stand for 30 minutes, then heating and leaving it to stand for 1 hour to obtain modified hemp stalk core powder, wherein the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1, the standing temperature is 20°C, the atmosphere of the heating and standing is a nitrogen atmosphere, and the nitrogen purge rate is 10 mL / min, and the temperature is 80°C;

[0024] Step 4, adding polyvinyl pyrrolidone to ethanol, then adding modified hemp stalk core powder, low-temperature ultrasound for 20 minutes, concentrating under reduced pressure to viscosity, filtering, drying and surface spraying to obtain filled hemp stalk core powder, the concentration of polyvinyl pyrrolidone in ethanol is 400g / L, the mass ratio of the modified hemp stalk core powder to polyvinyl pyrrolidine is 1:3, the ultrasonic frequency of low-temperature ultrasound is 80-100kHz, the temperature is 5°C, the temperature of the reduced pressure concentration is 70°C, the pressure is 80% of the atmospheric pressure, and the drying temperature is 80°C; the surface spraying uses distilled water, and the spraying speed is 10mL / min;

[0025] Step 5, adding ethyl cellulose and trichloromethylsilane to ether and stirring evenly to form a solution, and adding ammonium carbonate and filling hemp stalk core powder, stirring rapidly and then granulating and drying to obtain composite particles; the mass ratio of ethyl cellulose to trichloromethylsilane is 1:2, and the mass ratio of ethyl cellulose to ether is 1:6, the stirring speed is 300r / min, the ammonium carbonate is micron ammonium carbonate, and the addition amount is 40% of ethyl cellulose, the mass ratio of filling hemp stalk core powder to trichloromethylsilane is 1:0.8, the stirring speed of the rapid stirring is 2000r / min, the temperature of the granulation and drying is 50°C, and the particle size of the composite particles is 5mm;

[0026] Step 6: The composite particles are allowed to stand for 1 hour, and then trichloromethylsilane ether solution is sprayed on the surface of the composite particles, and then dried and allowed to stand for 1 hour to obtain prefabricated composite particles. The standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 10:1, the temperature is 5°C, the concentration of trichloromethylsilane in ether is 100g / L, and the spray volume is 2mL / cm 2The drying temperature after drying is 35° C., the atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 9:1;

[0027] Step 7, subjecting the prefabricated particles to a constant temperature treatment for 1-3 hours, and then placing them in ethanol for ultrasonic treatment for 20 minutes, taking them out and subjecting them to a constant temperature sintering treatment for 20 minutes, to obtain a hemp biomass insulating material, wherein the temperature of the constant temperature treatment is 70°C, the mass ratio of the ethanol to the prefabricated particles is 10:1, the temperature of the ultrasonic treatment is 20°C, the frequency is 70kHz, and the temperature of the constant temperature sintering is 400°C; the hemp biomass insulating material has hemp stalk core powder as the inner core, a porous silica film as the inner support frame, a porous silica structure as the outer expansion structure, and a silica material as the sealing surface membrane.

[0028] Example 2

[0029] A method for preparing a hemp biomass thermal insulation material comprises the following steps:

[0030] Step 1, grinding the hemp stalk core to obtain hemp stalk core powder with uniform particle size after sieving, the grinding pressure is 0.8 MPa, the temperature is 30° C., and the particle size of the hemp stalk core powder is 2 mm;

[0031] Step 2, adding trichloro(2-chloroethyl)silane to ether and stirring evenly, then putting in hemp stalk core powder and ultrasonically treating it for 30 minutes, filtering and drying to obtain coated hemp stalk core powder, the concentration of trichloro(2-chloroethyl)silane in ether is 140g / L, the stirring speed is 400r / min, the mass ratio of the hemp stalk core powder to the ether is 1:20, the temperature of ultrasonic treatment is 10°C, the ultrasonic frequency is 90kHz, the drying adopts reduced pressure drying, and the pressure is 90% of the atmospheric pressure, and the temperature is 25°C;

[0032] Step 3, leaving the coated hemp stalk core powder to stand for 60 minutes, then heating and leaving it to stand for 2 hours to obtain modified hemp stalk core powder, wherein the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 10:1, the standing temperature is 30°C, the atmosphere of the heating and standing is a nitrogen atmosphere, and the nitrogen purge rate is 20 mL / min, and the temperature is 90°C;

[0033] Step 4, adding polyvinyl pyrrolidone to ethanol, then adding modified hemp stalk core powder and performing low-temperature ultrasound for 30 minutes, concentrating under reduced pressure to viscosity, filtering, drying and surface spraying to obtain filled hemp stalk core powder, the concentration of polyvinyl pyrrolidone in ethanol is 600g / L, the mass ratio of the modified hemp stalk core powder to polyvinyl pyrrolidine is 1:4, the ultrasonic frequency of low-temperature ultrasound is 100kHz, the temperature is 10°C, the temperature of the reduced pressure concentration is 75°C, the pressure is 90% of the atmospheric pressure, and the drying temperature is 90°C; the surface spraying uses distilled water, and the spraying speed is 20mL / min;

[0034] Step 5, adding ethyl cellulose and trichloromethylsilane to ether and stirring evenly to form a solution, and adding ammonium carbonate and filling hemp stalk core powder, stirring rapidly and then granulating and drying to obtain composite particles; the mass ratio of ethyl cellulose to trichloromethylsilane is 1:4, and the mass ratio of ethyl cellulose to ether is 1:8, the stirring speed is 500r / min, the ammonium carbonate is micron ammonium carbonate, and the addition amount is 50% of ethyl cellulose, the mass ratio of filling hemp stalk core powder to trichloromethylsilane is 1:1.0, the stirring speed of the rapid stirring is 3000r / min, the temperature of the granulation and drying is 60°C, and the particle size of the composite particles is 6mm;

[0035] Step 6: The composite particles are allowed to stand for 3 hours, and then trichloromethylsilane ether solution is sprayed on the surface of the composite particles, and then dried and allowed to stand for 2 hours to obtain prefabricated composite particles. The standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 12:1, the temperature is 10°C, the concentration of trichloromethylsilane in ether is 200g / L, and the spray volume is 5mL / cm 2 The drying temperature after drying is 40° C., the atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 10:1;

[0036] Step 7, subjecting the prefabricated particles to a constant temperature treatment for 1-3 hours, and then placing them in ethanol for ultrasonic treatment for 30 minutes, taking them out and subjecting them to a constant temperature sintering treatment for 30 minutes, to obtain a hemp biomass insulating material, wherein the temperature of the constant temperature treatment is 90°C, the mass ratio of the ethanol to the prefabricated particles is 10:2, the temperature of the ultrasonic treatment is 40°C, the frequency is 90kHz, and the temperature of the constant temperature sintering is 450°C; the hemp biomass insulating material has hemp stalk core powder as the inner core, a porous silica film as the inner support frame, a porous silica structure as the outer expansion structure, and a silica material as the sealing surface membrane.

[0037] Example 3

[0038] A method for preparing a hemp biomass thermal insulation material comprises the following steps:

[0039] Step 1, grinding the hemp stalk core to obtain hemp stalk core powder with uniform particle size after sieving, the grinding pressure is 0.7 MPa, the temperature is 25° C., and the particle size of the hemp stalk core powder is 2 mm;

[0040] Step 2, adding trichloro(2-chloroethyl)silane to ether and stirring evenly, then adding hemp stalk core powder and ultrasonically treating it for 25 minutes, filtering and drying to obtain coated hemp stalk core powder, wherein the concentration of trichloro(2-chloroethyl)silane in ether is 130 g / L, the stirring speed is 300 r / min, the mass ratio of the hemp stalk core powder to the ether is 1:18, the temperature of the ultrasonic treatment is 8° C., the ultrasonic frequency is 80 kHz, and the drying adopts reduced pressure drying, and the pressure is 90% of the atmospheric pressure, and the temperature is 23° C.;

[0041] Step 3, leaving the coated hemp stalk core powder to stand for 50 minutes, then heating and leaving it to stand for 2 hours to obtain modified hemp stalk core powder, wherein the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 9:1, the standing temperature is 25°C, the atmosphere of the heating and standing is a nitrogen atmosphere, and the nitrogen purge rate is 15 mL / min, and the temperature is 85°C;

[0042] Step 4, adding polyvinyl pyrrolidone to ethanol, then adding modified hemp stalk core powder, low-temperature ultrasound for 25 minutes, concentrating under reduced pressure to viscosity, filtering, drying and surface spraying to obtain filled hemp stalk core powder, the concentration of polyvinyl pyrrolidone in ethanol is 500g / L, the mass ratio of the modified hemp stalk core powder to polyvinyl pyrrolidine is 1:4, the ultrasonic frequency of low-temperature ultrasound is 90kHz, the temperature is 8°C, the temperature of the reduced pressure concentration is 73°C, the pressure is 85% of the atmospheric pressure, and the drying temperature is 85°C; the surface spraying uses distilled water, and the spraying speed is 15mL / min;

[0043] Step 5, adding ethyl cellulose and trichloromethylsilane to ether and stirring evenly to form a solution, and adding ammonium carbonate and filling hemp stalk core powder, stirring rapidly and then granulating and drying to obtain composite particles; the mass ratio of ethyl cellulose to trichloromethylsilane is 1:3, and the mass ratio of ethyl cellulose to ether is 1:7, the stirring speed is 400r / min, the ammonium carbonate is micron ammonium carbonate, and the addition amount is 45% of ethyl cellulose, the mass ratio of filling hemp stalk core powder to trichloromethylsilane is 1:0.9, the stirring speed of the rapid stirring is 2500r / min, the temperature of the granulation and drying is 55°C, and the particle size of the composite particles is 6mm;

[0044] Step 6: The composite particles are allowed to stand for 2 hours, and then trichloromethylsilane ether solution is sprayed on the surface of the composite particles, and then dried and allowed to stand for 2 hours to obtain prefabricated composite particles. The standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 11:1, the temperature is 8°C, the concentration of trichloromethylsilane in ether is 150g / L, and the spray volume is 4mL / cm 2 The drying temperature after drying is 38° C., the atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 9:1;

[0045] Step 7, subjecting the prefabricated particles to a constant temperature treatment for 2 hours, then placing them in ethanol for ultrasonic treatment for 20-30 minutes, taking them out and subjecting them to a constant temperature sintering treatment for 25 minutes, to obtain a hemp biomass insulating material, wherein the temperature of the constant temperature treatment is 80°C, the mass ratio of the ethanol to the prefabricated particles is 10:2, the temperature of the ultrasonic treatment is 30°C, the frequency is 80kHz, and the temperature of the constant temperature sintering is 410°C; the hemp biomass insulating material has hemp stalk core powder as the inner core, a porous silica film as the inner support frame, a porous silica structure as the outer expansion structure, and a silica material as the sealing surface membrane.

[0046] Performance Testing

[0047] The thermal insulation materials of Examples 1-3 were used as test samples to prepare building materials for performance testing, and the results are as follows:

[0048] The preparation method of the test building material comprises:

[0049] Step 1, adding sodium hydroxide to sodium water glass to form an alkali activator, wherein the modulus of the sodium hydroxide and the sodium water glass is 2;

[0050] Step 2, blending fly ash with thermal insulation material, then adding alkali activator and stirring evenly, and obtaining building board after curing and hardening, wherein the mass ratio of fly ash, thermal insulation material and alkali activator is 1:0.4:0.6.

[0051] The performance tests of building panels are as follows:

[0052] Example 1 Example 2 Example 3 Thermal conductivity W / m*K 0.13 0.09 0.11 Compression strength 16MPa 18MPa 17MPa Combustion performance level B1 B1 B1

[0053] It is understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.

Claims

1. A method for preparing a hemp biomass thermal insulation material, characterized in that: The steps include: Step 1, grinding the hemp stalk core and obtaining hemp stalk core powder with uniform particle size after sieving; Step 2, adding trichloro(2-chloroethyl)silane to ether and stirring evenly, then adding hemp stalk core powder and ultrasonically treating for 20-30 minutes, filtering and drying to obtain coated hemp stalk core powder; Step 3, allowing the coated hemp stalk core powder to stand for 30-60 minutes, and then heating and allowing to stand for 1-2 hours to obtain modified hemp stalk core powder; Step 4, adding polyvinyl pyrrolidone to ethanol, then adding modified hemp stalk core powder, ultrasonicating at low temperature for 20-30 minutes, concentrating under reduced pressure until viscous, filtering, drying and surface spraying to obtain filled hemp stalk core powder; Step 5, adding ethyl cellulose and trichloromethylsilane to ether and stirring evenly to form a solution, and adding ammonium carbonate and hemp stalk core powder, stirring rapidly, granulating and drying to obtain composite particles; Step 6, allowing the composite particles to stand for 1-3 hours, then spraying trichloromethylsilane ether solution on the surface of the composite particles, drying and allowing to stand for 1-2 hours to obtain prefabricated composite particles; Step 7, subjecting the prefabricated particles to a constant temperature treatment for 1-3 hours, and then subjecting the prefabricated particles to an ultrasonic treatment for 20-30 minutes, and then subjecting the prefabricated particles to a constant temperature sintering treatment for 20-30 minutes to obtain a hemp biomass insulating material.

2. The method for preparing the hemp biomass thermal insulation material according to claim 1, characterized in that: The grinding pressure in step 1 is 0.5-0.8 MPa, the temperature is 20-30° C., and the particle size of the hemp stalk core powder is 1-2 mm.

3. The method for preparing the hemp biomass thermal insulation material according to claim 1, characterized in that: The concentration of trichloro(2-chloroethyl)silane in diethyl ether in step 2 is 100-140 g / L, the stirring speed is 200-400 r / min, the mass ratio of the hemp stalk core powder to diethyl ether is 1:15-20, the temperature of the ultrasonic treatment is 5-10°C, the ultrasonic frequency is 70-90 kHz, and the drying adopts reduced pressure drying, and the pressure is 90% of the atmospheric pressure, and the temperature is 20-25°C.

4. The method for preparing the hemp biomass thermal insulation material according to claim 1, characterized in that: The standing atmosphere in step 3 is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8-10:1, the standing temperature is 20-30°C, and the atmosphere for heating and standing is a nitrogen atmosphere, and the nitrogen purge rate is 10-20mL / min, and the temperature is 80-90°C.

5. The method for preparing the hemp biomass thermal insulation material according to claim 1, characterized in that: The concentration of polyvinyl pyrrolidone in ethanol in step 4 is 400-600g / L, the mass ratio of the modified hemp stalk core powder to polyvinyl pyrrolidine is 1:3-4, the ultrasonic frequency of low-temperature ultrasound is 80-100kHz, the temperature is 5-10°C, the temperature of the reduced pressure concentration is 70-75°C, the pressure is 80-90% of the atmospheric pressure, and the temperature of the drying is 80-90°C; distilled water is used for surface spraying, and the spraying speed is 10-20mL / min.

6. The method for preparing the hemp biomass thermal insulation material according to claim 1, characterized in that: The mass ratio of ethyl cellulose to trichloromethylsilane in step 5 is 1:2-4, and the mass ratio of ethyl cellulose to ether is 1:6-8, the stirring speed is 300-500r / min, the ammonium carbonate is micron ammonium carbonate, and the addition amount is 40-50% of the ethyl cellulose, the mass ratio of the hemp stalk core powder to trichloromethylsilane is 1:0.8-1.0, the stirring speed of the rapid stirring is 2000-3000r / min, the temperature of the granulation and drying is 50-60°C, and the particle size of the composite particles is 5-6mm.

7. The method for preparing the hemp biomass thermal insulation material according to claim 1, characterized in that: The static atmosphere in step 6 is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 10-12:1, the temperature is 5-10°C, the concentration of trichloromethylsilane in ether is 100-200g / L, and the spray volume is 2-5mL / cm 2 The drying temperature after drying is 35-40° C., the atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 9-10:

1.

8. The method for preparing the hemp biomass thermal insulation material according to claim 1, characterized in that: The temperature of the constant temperature treatment in step 7 is 70-90°C, the mass ratio of the ethanol to the prefabricated particles is 10:1-2, the temperature of the ultrasonic treatment is 20-40°C, the frequency is 70-90kHz, and the temperature of the constant temperature sintering is 400-450°C.

9. The method for preparing the hemp biomass thermal insulation material according to claim 1, characterized in that: The hemp biomass insulation material in step 7 has hemp stalk core powder as the inner core, a porous silica film as the inner support frame, a porous silica structure as the outer expansion structure, and a silica material as the sealing surface membrane.